Investigating the Role of Entrepreneurship on the Empowerment of Women Heads of Households Covered by Dezful welfare (a case study of Women Heads of Dezful welfare Households) - Halajan, Azimeh; Omidian, Faranak; Hosseinpour, Mohammad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: women heads of poor households are one of the vulnerable groups of society, and due to the increasing growth of their numbers in recent years, how to deal with various issues affecting their lives has become an important challenge in Iran. Therefore, empowering this group to participate in various jobs is very important. Therefore, the purpose of the present study was to investigate the effect of entrepreneurship on the empowerment of female heads of households in Dezful city. Methods: The current research method is descriptive and correlational. The statistical population of the research was all women heads of households in Dezful city who had entered the empowerment and entrepreneurship plan in Dezful welfare organization during the years 2006 to 2021. This community included 44 households, all of which (all census) were selected as sampling. In order to collect the investigated data, questionnaires of culture and economic and social factors affecting women's entrepreneurship were used by Beech (2007) and empowerment of women by Gupta and Srivatava (2011). The resulting data were analyzed by statistical methods (multiple correlation analysis). Results: The research findings showed that there is a positive and significant relationship between entrepreneurship and women's empowerment. The correlation coefficient of two variables was (R=0.52) and the significance level was (P